(untitled) (In Factis Pax: Journal of Peace Education and Social Justice, 2021)
I learned many important lessons about life as a Detroit Police Officer. I learned that there is a lot of good in the world. I witnessed a goodness that stems from a collective spirit of togetherness. Detroiters are resilient. In the face of poverty, institutional racism, classism, violence and a crumbling educational system, Detroiters find a way to persevere despite odds that might appear to be insurmountable (at least on the surface). Inscribed on the flag that represents the city of Detroit is a Latin saying that I believe captures the true spirit of the city of Detroit: Speramus meliora; resurget cineribus, we hope for better things, it shall arise from the ashes. Detroit is a resilient city, a city that has seen race riots, violence, collapse of the automotive industry, bankruptcy and a football team that has been the laughingstock of the National Football League. I am a proud Detroiter and I am happy to say that the city is my home.